Book reviews. - Smith, David M.; Garshick Kleit, Rachel; Morris, Lydia; Daniels, Mark R.; Harpham, Edward J.; Hubbard, Phil; Osayimwese, Itohan; Martin, David (Urban Studies (Routledge), 2004)
Reviews several books. "Clearing the Way: Deconcentrating the Poor in Urban America," by Edward G. Goetz; "Urban Bonds: Social Relationships in an Inner City Neighbourhood," by Talja Blokland; "Civic Culture and Urban Change: Governing Dallas," by Royce Hanson.